NUTRIENT PHOSPHATE, NITRATE AND SILICATE DISTRIBUTION OF NATUNA ARCHIPELAGO WATERS - Muswerry Muchtar (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2012)
Research on phosphate, nitrate and silicate distributions of Natuna ArchipelagoWaters was conducted using RV Baruna Jaya VIII in April  2011.  Concentration of phosphate, nitrate and silicate were analyses by Spectrophotometry. The purpose of the study was to assess  the distribution of nutrients as fertility indicator of marine life. The results showed that the phosphate concentration at surface layer of Subi, Bunguran,  and Laut islands ranged from 0,04 to 0,22 µg A/l, 0,04 to 0,18 µg A/l and from 0,04 to 0,13 µg A/l, with average  0,11 µgA/l, 0,08 µgA/l and  0,07 µg A/l,  respectivelly. Concentration of nitrate ranged from 0,31 to 4,90 µg A/l, 0,23 to 2,29 µg A/l and from 0,14 to 0,32   µg A/l with average of 90 µgA/l, 0,78 µg A/l and  0,22 µg A/l, respectivelly. Silicate concentration  ranged from 2,97 to 5,35  µg A/l, 2,28 to 4,85  µg A/l and from 2,28 to 3,57 µg A/l with average  4,49 µgA/l, 3,62 µg A/l and 3,02 µg A/l,respectivelly. While phosphate concentration at bottom layer of Subi, Bunguran  and Laut  islands ranged from 0,04-0,27 µg A/l,  0,04-0,31 µg A/l and 0,09-0,22µg A/l,, with average  0,13 µgA/l, 0,13 µgA/l dan 0,12, µg A/l  respectivelly. Concentration of nitrate  ranged  from 2,59-5,61µg A/l, 0,73-4,75 µg A/l and 2,06-3,03 µg A/l with average  2,85 µgA/l, 3,14 µg A/l and 2,49 µg A/ respectivelly. Silicate concentration in Subi, Bunguran and Laut Islands ranged from  4,46-6,21 µg A/l, 3,20-5,84  µg A/l dan 3,07-4,66 µg A/l with average 5,323,73 µgA/l, 4,74 µg A/l dan 3,73 µg A/l. In general concentration of those nutrient of Natuna Archipelago waters  was still within the Standard Quality set by the Ministery of Environment (KMNLH). Keywords: nutrient, phosphate, nitrate, silicate, Natuna Archipelago waters.